2010
DOI: 10.1071/an09145
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of grazing management options on pasture and animal productivity in a Heteropogon contortus (black speargrass) pasture in central Queensland. 4. Animal production

Abstract: Steer liveweight gains were measured in an extensive grazing study conducted in a Heteropogon contortus (black speargrass) pasture in central Queensland between 1988 and 2001. Treatments included a range of stocking rates in native pastures, legume-oversown native pasture and animal diet supplement/spring‐burning pastures. Seasonal rainfall throughout this study was below the long-term mean. Mean annual pasture utilisation ranged from 13 to 61%. Annual liveweight gains per head in native pasture were highly va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Variation in the amount and timing of rainfall caused large variations in liveweight gain between years, ranging from 74 kg/head in drought years to 192 kg/head (mean of 146) in the Control paddock, from 102 to 224 kg/head (mean of 169) in Rehab 2, and from 56 to 176 kg/head (mean of 130) for the shallow soil BMK 2 site with limited soil water holding capacity. Variability of liveweight gain caused by seasonal weather conditions is typical of pastures in the Brigalow Region (Bortolussi et al 2005a;Radford et al 2007;Burrows et al 2010) and was observed during the trial as large changes in liveweight gain during the year (from -0.26 to 1.62 kg/head. day; Melland et al 2021).…”
Section: Effects Of Climate On Productivity and Economic Returnsmentioning
confidence: 99%
“…Variation in the amount and timing of rainfall caused large variations in liveweight gain between years, ranging from 74 kg/head in drought years to 192 kg/head (mean of 146) in the Control paddock, from 102 to 224 kg/head (mean of 169) in Rehab 2, and from 56 to 176 kg/head (mean of 130) for the shallow soil BMK 2 site with limited soil water holding capacity. Variability of liveweight gain caused by seasonal weather conditions is typical of pastures in the Brigalow Region (Bortolussi et al 2005a;Radford et al 2007;Burrows et al 2010) and was observed during the trial as large changes in liveweight gain during the year (from -0.26 to 1.62 kg/head. day; Melland et al 2021).…”
Section: Effects Of Climate On Productivity and Economic Returnsmentioning
confidence: 99%
“…Results from a 13-year stocking rate experiment using paddock sizes of 10 -40 ha in central Queensland showed that profitability was greatest at the heaviest stocking rate with an average pasture utilisation rate of about 61 % (Burrows et al 2010). Although rainfall over the trial period was generally well below average, no major pasture composition change occurred.…”
Section: Empirical Evidence For Stocking At Ltccmentioning
confidence: 99%
“…However, all involved relatively small, uniform paddocks of between 3 and 30 ha, with small groups of animals (e.g. Burrows et al, 2010;Ash et al, 2011). This lack of scale and spatial complexity limits their relevance to larger, more heterogeneous commercial paddocks where production and rangeland responses may be significantly different (Ash and Stafford Smith, 1996).…”
Section: Insights From Grazing Trialsmentioning
confidence: 99%